2021
DOI: 10.3390/polym13081292
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Application of Matrimid® and ZIFs-Based Membranes for Hydrogen Recovery: A Review

Abstract: Hydrogen recovery is at the center of the energy transition guidelines promoted by governments, owing to its applicability as an energy resource, but calls for energetically nonintensive recovery methods. The employment of polymeric membranes in selective gas separations has arisen as a potential alternative, as its established commercial availability demonstrates. However, enhanced features need to be developed to achieve adequate mechanical properties and the membrane performance that allows the obtention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 103 publications
(216 reference statements)
0
8
0
Order By: Relevance
“…Khan et al found an increase by 2.3 times in the H 2 /CO 2 selectivity with 40 wt % of zeolite 3A incorporated into polysulfone acrylate membranes. ZIFs (Zeolitic Imidazole Frameworks) a subset of MOFs, which easily interact with polymers and facilitate hydrogen permeation flux, have been also investigated as fillers . Addition of ZIF-8 to different polymers provides higher H 2 /N 2 , H 2 /CH 4 , and H 2 /CO selectivity, while the selectivity of binary H 2 /CO 2 mixtures slightly increases compared to the pristine Matrimid polymer, because the pore size of the ZIF-8 (3.4 Å) is placed between H 2 , CO 2 , and bulk compounds: N 2 (3.64 Å), CO (3.76 Å), CH 4 (3.8 Å). Besides, Diestel et al reported an increase in H 2 /CO 2 selectivity with ZIF-90 in the Matrimid polymer matrix.…”
Section: Hydrogen Recovery From Coke Oven Gasmentioning
confidence: 99%
“…Khan et al found an increase by 2.3 times in the H 2 /CO 2 selectivity with 40 wt % of zeolite 3A incorporated into polysulfone acrylate membranes. ZIFs (Zeolitic Imidazole Frameworks) a subset of MOFs, which easily interact with polymers and facilitate hydrogen permeation flux, have been also investigated as fillers . Addition of ZIF-8 to different polymers provides higher H 2 /N 2 , H 2 /CH 4 , and H 2 /CO selectivity, while the selectivity of binary H 2 /CO 2 mixtures slightly increases compared to the pristine Matrimid polymer, because the pore size of the ZIF-8 (3.4 Å) is placed between H 2 , CO 2 , and bulk compounds: N 2 (3.64 Å), CO (3.76 Å), CH 4 (3.8 Å). Besides, Diestel et al reported an increase in H 2 /CO 2 selectivity with ZIF-90 in the Matrimid polymer matrix.…”
Section: Hydrogen Recovery From Coke Oven Gasmentioning
confidence: 99%
“…PMP filling with nanoparticles and the creation of mixed matrix membranes (MMM)s can improve the CO 2 permeability and CO 2 /CH 4 selectivity, which was demonstrated in [16,42]. These data added in Figure 8 show that PMP-based MMMs can potentially reach the selectivity level of commercial polymers, which are used for the production of gas separation membranes: polyimides (Matrimid ®® and Kapton ®® ) [43,44], cellulose acetate and polysulfone [45]. However, the influence of such PMP modification on the HF melt spinning process has to be studied, and the change in the HFs' mechanical properties has to be taken into account in order to withstand further braiding or weaving.…”
Section: Discussionmentioning
confidence: 90%
“…The characteristics that these polymers must fulfil to have a good performance are, above all, a high permeate flux and a high selectivity. In addition, they must also have high mechanical strength, high temperature resistance, chemical stability, and easy processability [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%